Biocontrol potential of Chitinophaga flava HK235 producing antifungal-related peptide chitinocin - Kim, Da Yeon; Han, Jae Woo; Lee, Jin Woo; Kim, Bomin; Kim, Yeong Seok; Kim, Heung-Tae; Choi, Gyung Ja; Kim, Hun (Frontiers in Microbiology, 2023)
Botrytis cinerea is a necrotrophic fungal pathogen with an extremely broad host range, causing significant economic losses in agricultural production. In this study, we discovered a culture filtrate of bacterial strain HK235, which was identified as Chitinophaga flava, exhibiting high levels of antifungal activity against B. cinerea. From the HK235 culture filtrate, we isolated a new antimicrobial peptide molecule designated as chitinocin based on activity-guided fractionation followed by characterization of the amino acid composition and spectroscopic analyses. The HK235 culture filtrate and chitinocin completely inhibited both conidial germination and mycelial growth of B. cinerea at a concentration of 20% and 200 μg/mL, respectively. In addition to antibiosis against B. cinerea, the active compound chitinocin had a broad antifungal and antibacterial activity in vitro. When tomato plants were treated with the culture filtrate and chitinocin, the treatment strongly reduced the development of gray mold disease in a concentration-dependent manner compared to the untreated control. Here, considering the potent antifungal property in vitro and in vivo, we present the biocontrol potential of C. flava HK235 for the first time.